Mechanisms of photoinduced toxicity of AgNPs to the microalgae Chlorella pyrenoidosa in the presence of hematite nanoparticles: insights from transcriptomics, metabolomics and the photochemical index. Issue 9 (19th August 2022) - Cao, Manman; Wang, Fei; Zhou, Beihai; Chen, Huilun; Yuan, Rongfang; Ma, Shuai; Geng, Huanhuan; Xing, Baoshan
Abstract : AgNPs attachment to HemNPs have caused photoinduced cytotoxicity, elevating the AgNPs toxicity to  C. pyrenoidosa  by producing free radicals and improving photocatalytic activity under illumination. Abstract : Silver nanoparticles (AgNPs) have little impact on organisms at environmentally relevant concentrations. However, AgNPs coexisting with photoactive minerals may show an elevated combined ecotoxicity due to the additional photoinduced cytotoxicity caused by the Ag loading, which increases the photocatalytic activity. Herein, key pathway perturbations in the algae Chlorella pyrenoidosa ( C. pyrenoidosa ) under exposure to AgNPs, hematite nanoparticles (HemNPs), and their mixtures (direct exposure (MX1) and exposure after interaction (MX2)) were explored under illumination using transcriptomic and metabolomic approaches. The results showed that the MX2 group exhibited the strongest C. pyrenoidosa growth inhibition. The AgNPs, HemNPs, MX1 and MX2 groups significantly triggered ROS production in algal cells, which increased by 11.05%, 5.54%, 4.79% and 13.58%, respectively. Notably, the cell membrane was obviously damaged only in the MX2 group. Transcriptomic and metabolomic analyses showed that metabolic pathways, such as starch and sucrose metabolism, pantothenate and CoA biosynthesis, and amino acid metabolism, were significantly altered. To examine the internal mechanisms behind these differences in genes and metabolites, ultraviolet–visible (UV–vis) diffuse reflectance spectroscopy, electrochemical impedance spectroscopy (EIS) and photocurrent response measurements were used to determine the photochemical properties of the four systems. AgNPs attachment enhanced the photoelectric properties of the AgNPs/HemNPs composite (MX2), improving the photoinduced electron–hole pair separation efficiency and charge separation efficiency. Electron paramagnetic resonance (EPR) results also showed that the MX2 system yielded the highest amount of free radicals. Free radicals caused photoinduced cytotoxicity in algae, leading to aggravated toxicity of AgNPs to C. pyrenoidosa in the presence of HemNPs.